A 130 GHz Fully-Integrated Fundamental-Frequency D-Band Transmitter Module with > 4 dBm Single-Ended Output Power - Aguilar, Erick; Issakov, Vadim; Weigel, Robert (IEEE Transactions on Circuits and Systems II: Express Briefs, 2020)
A 130 GHz fully-integrated fundamental-frequency transmitter (TX) module with 4.4 dBm single-ended measured output power in a 130 nm SiGe technology is presented. The transmitter achieves in measurement a phase noise of-88 dBc/Hz at 1 MHz offset frequency from a 130 GHz carrier and a tuning range of 17 GHz. Its relatively compact size, low power consumption and high output power, enables the TX module to be integrated into more complex D-Band transceiver modules for radar and imaging applications. Due to the available measurement equipment, it was only possible to measure the output power single-ended. The measured single-ended output power is 4.4 dBm. This corresponds well to a simulated maximum differential output power of 8.1 dBm. To the best of the author's knowledge, the presented chip exhibits one of the highest output power for fundamental-frequency TX modules among the recently reported state-of-The art chips in this frequency range.
CRIS-Team Scopus Importer:2020-05-22
Keywords: BiCMOS integrated circuits; imaging; Millimeter-wave integrated circuits; radar; transmitters

A 130 GHz Fully-Integrated Fundamental-Frequency D-Band Transmitter Module with > 4 dBm Single-Ended Output Power - Aguilar Mendoza, Erick; Issakov, Vadim; Weigel, Robert (2020 International Symposium on Circuits and Systems (ISCAS), 2020)
A 130 GHz fully integrated fundamental frequency transmitter (TX) module with 4.4 dBm single-ended measured output power in a 130 nm SiGe technology is presented. The transmitter achieves in measurement a phase noise of -88 dBc/Hz at 1 MHz offset frequency from a 130 GHz carrier and a tuning range of 17 GHz. Its relatively compact size, low power consumption and high output power, enables the TX module to be integrated into more complex D-Band transceiver modules for radar and imaging applications. Due to the available measurement equipment, it was only possible to measure the output power single-ended. The measured single-ended output power is 4.4 dBm. This corresponds well to a simulated differential output power of 8.1 dBm.Based on simulation results, the TX module can produce a maximum output power of 8.1 dBm. To the best of the author’s knowledge, the presented chip exhibits the highest output power fundamental frequency TX module among the recently reported state-of-the art chips in this frequency range. <br

A 155 GHz Low-Power Total Power Radiometer in a 130 nm SiGe Technology - Aguilar Mendoza, Erick; Hagelauer, Amelie Marietta; Weigel, Robert (11th German Microwave Conference (GeMiC), 2018)
A low-power total power radiometer for passive imaging applications is presented. The radiometer is manufactured in a 130 nm SiGe technology with an f t /f max of 250/370 GHz. The radiometer achieves a minimum noise equivalent temperature difference (NETD) of 0.21 K at 155 GHz. By optimization of the building blocks and biasing stages, a low-power system with a total power consumption of 64 mW is achieved. Due to its low NEP and low-power consumption, the system enables further integration into high-density sensor arrays for passive radiometry in the D-Band.<br
Keywords: mm-wave; D-Band; Radiometer; Total Power Radiometer; Imaging

A fundamental-frequency 122 GHz radar transceiver with 5.3 dBm single-ended output power in a 130 nm SiGe Technology - Aguilar, Erick; Issakov, Vadim; Weigel, Robert (IEEE MTT-S International Microwave Symposium Digest, 2020)
A fundamental-frequency D-Band transceiver (TRX) module in a 130 nm SiGe HBT technology for radar applications is presented. The module achieves in measurements a phase noise of -89 dBcI/Hz at an offset frequency of 1 MHz with an output frequency of fTX=122 GHz and operates in the frequency range of 110 - 125 GHz. A measured maximum conversion gain (CG) of 8.5 dB at fIF = 1 GHz is observed. Due to limitations of available measurement equipment, the output power had to be measured in a single-ended manner. Under this consideration, an output power of 5.3 dBm is measured, which to the best of the author's knowledge, corresponds to the highest output power reported so far for a fully-integrated fundamental-frequency-based TRX module including on-chip LO generation in the 120 GHz frequency range. By employing a differential antenna at the output, the TRX can potentially generate an effective output power of about 8 dBm.
CRIS-Team Scopus Importer:2020-11-06
Keywords: D-Band; Fundamental-frequency; High-power; Highly-integrated; SiGe; Transceiver; TRX

A Low-Power Wideband D-Band LNA in a 130 nm BiCMOS Technology for Imaging Applications - Aguilar Mendoza, Erick; Hagelauer, Amelie Marietta; Kissinger, Dietmar; Weigel, Robert (Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2018)
A Low-power D-Band Low Noise Amplifier (LNA) manufactured in a recent 130 nm SiGe BiCMOS process for imaging applications is presented. The architecture consists of an optimized 3-stage cascode amplifier which achieves a maximum gain of 32.8 dB and a gain>20 dB in the frequency range from 121 to 161 GHz with a DC power consumption of 39.6 mW. The simulated noise figure varies from 6 to 9.7 dB within the range 130 to 140 GHz. To the best of the author’s knowledge, the presented work exhibits the highest gain-bandwidth product with the lowest power consumption for a D-Band amplifier in a 130 nm SiGe technology.
Keywords: D-Band; Imaging; Radiometrie; LNA; SiGe; mm-wave

Considerations on Accurate Characterization of Differential Devices Using Baluns - Issakov, Vadim; Sene, Badou; Aguilar Mendoza, Erick; Werthof, Andreas; Jenei, Snezana; Weigel, Robert (European Microwave Conference, 2017)
Direct characterization of differential components requires multiport equipment, which is not always available. Thus, it is a common practice to attach balanced-unbalanced (balun) circuits to convert between single-ended and differential signals. However, removing impact of baluns from measured two-port S-parameters is a challenge, since baluns are threeport devices and classical de-embedding techniques are not applicable. Additionally, obtaining the S-parameters of baluns by two-port network analyzer is not trivial, since the ports at the differential side are tightly coupled. In this paper we address both challenges by proposing two techniques: how to characterize a balun using two-port measurements, and how to accurately de-embed the impact of balun characteristics from device-undertest (DUT) measurements. The applicability and accuracy of the proposed techniques is analyzed. For verification, the first technique has been applied to characterize an integrated ultrawideband (UWB) Marchand balun, and the second to de-embed the baluns impact from measured results of the balun-DUTbalun structure. The characterized DUT is a differential LNA operating in the range from 30 GHz to 110 GHz realized in 0.35 μm SiGe:C bipolar technology. The obtained de-embedded S-parameters are compared with the directly measured results<br
Keywords: S-Parameter; Balun; LNA

Highly-Integrated Scalable D-band Receiver Frontend Modules in a 130 nm SiGe Technology for Imaging and Radar Applications - Aguilar Mendoza, Erick; Issakov, Vadim; Weigel, Robert (2020 German Microwave Conference (GeMiC), 2020)
Two highly integrated, scalable D-Band receiver front-ends based on active and passive baluns which integrate a D-Band signal generator developed in a 130 nm SiGe technology are presented. The presented circuits exhibit a wide tuning range of 19 GHz around 110 GHz and achieve high conversion gains >20 dB and >12 dB for the active-based an passive-based approaches correspondingly. The new chips offer robust solutions for high-gain or high-linearity receivers while showing an extremely compact form factor. Both chips show competitive performance compared with state-of-the-art solutions. Due to their highly reduced area without compromising the power consumption, they can be directly integrated into high-density sensor arrays for imaging and radar applications. <br